Unearthing St. Mary's city : fifty years of archaeology at Maryland's first capital - Miller, Henry M. (Henry Michael); Parno, Travis G.; Kelso, William M. (University Press of Florida, 2021)
"This volume summarizes the remarkably diverse archaeological discoveries made during the past half century of investigations at the site of St. Mary's City, the first capital of Maryland and one of the earliest European settlements in America"--